Targeting cell spreading: a method of sensitizing metastatic tumor cells to TRAIL-induced apoptosis. - Phipps, L; Hino, S; Muschel, R (2011)
TNF-related apoptosis-inducing ligand (TRAIL) is a current focus for the development of new cancer therapies, because of its selective induction of apoptosis in cancer cells. TRAIL has previously been shown to be important for tumor cell clearance from the liver; however, many cancer cell lines show some resistance toward TRAIL, posing a problem for the future use of TRAIL therapies. In this study, we show that interfering with a cell's ability to attach and spread onto a matrix can sensitize tumor cells to TRAIL-induced apoptosis in vitro. We targeted different members of the integrin signaling pathway using siRNA or inhibitors, including β-integrins, talin, Src, and downstream survival pathways PI3K and MAPK. Targeting any of these molecules could sensitize both MDA-MB-231 human breast cancer cells and TRAIL-resistant 1205Lu melanoma cells to TRAIL-induced apoptosis in vitro. Transcriptionally targeting the cytoskeleton, using myocardin-related transcription factor depletion to disrupt the transcription of cytoskeletal proteins, also caused TRAIL sensitization in MDA-MB-231 cells. We showed that this sensitivity to TRAIL correlated with increased activation of the intrinsic pathway of apoptosis. Manipulation of cell spreading therefore presents a potential method by which disseminated tumor cells could be sensitized to TRAIL therapies in vivo.